Regulation of Pyroptosis by ncRNA: A Novel Research Direction - Gao, Liyuan; Jiang, Zhitao; Han, Yi; Li, Yang; Yang, Xiang (Frontiers in Cell and Developmental Biology, 2022)
Pyroptosis is a novel form of programmed cell death (PCD), which is characterized by DNA fragmentation, chromatin condensation, cell swelling and leakage of cell contents. The process of pyroptosis is performed by certain inflammasome and executor gasdermin family member. Previous researches have manifested that pyroptosis is closely related to human diseases (such as inflammatory diseases) and malignant tumors, while the regulation mechanism of pyroptosis is not yet clear. Non-coding RNA (ncRNA) such as microRNA (miRNA), long non-coding RNA (lncRNA) and circular RNA (circRNA) have been widely identified in the genome of eukaryotes and played a paramount role in the development of cell function and fate after transcription. Accumulating evidences support the importance of ncRNA biology in the hallmarks of pyroptosis. However, the associations between ncRNA and pyroptosis are rarely reviewed. In this review, we are trying to summarize the regulation and function of ncRNA in cell pyroptosis, which provides a new research direction and ideas for the study of pyroptosis in different diseases.